Analysis of the Influence of Service Quality and Customer Satisfaction on Customer Loyalty at Kopi Janji Jiwa, Jilid 738, Gunungsitoli City - Indah Kristin Reformani Waruwu; Yuterlin Zalukhu (JURNAL ECONOMINA, 2026)
This study aims to analyze the influence of service quality and customer satisfaction on customer loyalty at Kopi Janji Jiwa Jilid 738 in Gunungsitoli City. This study employs a quantitative approach. The study population consists of customers of Kopi Janji Jiwa Jilid 738 in Gunungsitoli City during the period from October 2024 to November 2024, estimated to number 150 people. The research sample consisted of 30 respondents. Data collection was conducted using a questionnaire with a Likert scale. The data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient tests, F-tests, and t-tests with the assistance of SPSS version 26. The results showed that all statement items were valid and reliable. An R value of 0.918 indicates a very strong relationship between service quality and customer satisfaction, collectively influencing customer loyalty. An R-squared value of 0.843 indicates that 84.3% of the variation in customer loyalty can be explained by service quality and customer satisfaction, while the remaining 15.7% is influenced by other variables outside the scope of this study. The results of the F-test show that service quality and customer satisfaction simultaneously have a significant effect on customer loyalty. Partially, service quality has a positive and significant effect on customer loyalty with a calculated t-value of 4.852 and a significance level of 0.000. Meanwhile, customer satisfaction does not have a significant partial effect on customer loyalty, with a t-value of 0.535 and a significance level of 0.597. Thus, service quality is the most dominant variable influencing customer loyalty at Kopi Janji Jiwa Jilid 738 in Gunungsitoli.